Metabolic variation and cooking qualities of millet cultivars grown both organically and conventionally. (April 2018) - Liang, Kehong; Liang, Shan; Lu, Lingang; Zhu, Dazhou; Zhu, Hong; Liu, Peng; Zhang, Min
Abstract: Millet plays a major role in food security in Africa and Asia. In addition to being a rich source of nutrients, millet contains many phytochemicals that are potentially beneficial for human health, and several of these compounds are related to its cooking properties. In this study, 172 metabolites and 3 cooking quality traits of millet from the same two cultivars grown both organically and conventionally were analyzed. The results indicated that the differences in the metabolities and cooking quality of the millets could be attributed mostly to the cultivar and whether the millet was grown conventionally or organically. Organic growing conditions only enhanced the accumulation of some carbohydrates such as fructose and glucose. Therefore, cultivar selection was important in organic millet cultivation. The relationships between metabolites and cooking quality traits showed that, overall, 57.43% of the variation in the cooking quality matrix was explained by metabolome matrix, which indicated that some chemical compounds could also be used to evaluate the cooking qualities of millet. These results could contribute to breeding millet to improve its the nutritional properties and cooking qualities. Graphical abstract: Unlabelled Image Highlights: Organic and conventional millets were analyzed based on metabolomics. For the first time non-targeted metabolomics was applied to millet. 57.43% of the variation in the cooking quality matrix was explained by metabolome matrix.